AUXINS APPLICATION ON PROPAGATION OF OLIVE C.V. CHEMLALI BY SEMI-HARDWOOD CUTTINGS - Ayad H.Esmaeel Al-Allaf (Mesopotamia Journal of Agriculture)
This research was conducted at plastic house in Horticulture Dept. of Agriculture and Forestry College , University of Mosul during 2007-2008 season .To study the effect of three dates 20 Dec , 1 Feb , 10 March and the effect of Auxin treatments 0 ppm , 2000 ppm IBA , 2000 ppm NAA and 2000 ppm IBA + 2000 ppm NAA on propagation of semi- hardwood of Olive cutting Cv. Chemlali . The obtained results could be summarized as follows : A significant effect of the date of cutting planting on the root percentage and the date of 10 march was the most effective date on root percentage , number of root , length of root and number of leaves. The high percentage of living unrooted cutting the date of 20 Dec which 41,66%. All auxin treatments significantly increased on all vegetative and root growth characteristics and the best treatments was when applied auxin as a mixture 2000 ppm IBA + 2000 ppm NAA. The more effective interaction treatments between 2000 ppm IBA auxin and date of planting was 10 March which 93.33% of root percentage , followed by treatments of a mixture between 2000 ppm IBA + 2000 ppm NAA when planted at 10 March which 90% both interaction treatments significant increased as compared with interaction treatments.